The association between soy intake and risk of gestational diabetes mellitus: a prospective cohort study - Yan Wang; Biru Luo; Jie Xiang (BMC, 2021)
Abstract Background The association between soy intake and adverse pregnancy outcomes remains unclear. The objectives of this study were to investigate the soy consumption of pregnant women in the second trimester and explore the prospective association between soy intake and the risk of adverse pregnancy outcomes. Methods Pregnant women between 13 and 24 weeks of gestation were recruited at a women's and children's hospital in southwest China from June to December 2019. Dietary intakes in the middle trimester were assessed by a semi-quantitative food frequency questionnaire. Participants were divided into the insufficient group (< 40 g/day) and the control group (≥40 g/day) according to daily soy consumption. Participants were followed up until delivery. Pregnancy outcomes including gestational diabetes mellitus (GDM), cesarean section, and macrosomia were obtained. Multiple logistic regression was used to analyze the association between soy intake and risk of adverse pregnancy outcomes. Sociodemographic information, histories of diseases, and duration of physical activities were obtained and used for covariate adjustments. Results A total of 224 participants were included in this study, of which identified 36 (16.1%) cases of GDM, and 120 (53.6%) cases of cesarean section. More than half (125, 55.8%) pregnant women consumed less soy than 40 g/day. Daily soy intake less than 40 g was associated with the increased risk of GDM (OR = 2.755 95%CI 1.230-6.174, P = 0.014) and cesarean section (OR = 1.792 95%CI 1.035-3.101, P = 0.037) without adjustment for confounders such as age, pre-pregnancy body mass index, parity, daily intake of vegetables, fruits, seafood and, nuts. After adjusting for these factors, daily soy intake of less than 40 g increased 2.116-fold risk of GDM (95%CI 1.228-7.907, P = 0.017), but not with the significantly increased risk of cesarean section. Conclusion Insufficient soy intake may increase the risk of GDM, suggesting adequate soy intake may have a beneficial role in the prevention of GDM. Trial registration Registration number: ChiCTR1900023721 . Date of registration: June 9, 2019.